2002
DOI: 10.1046/j.1464-4096.2001.001217.x
|View full text |Cite
|
Sign up to set email alerts
|

Transurethral needle ablation for chronic nonbacterial prostatitis

Abstract: Objective To investigate the ef®cacy of transurethral needle ablation (TUNA) of the prostate for treating chronic nonbacterial prostatitis unresponsive to conservative therapies. Patients and methods Forty-two patients (mean age 38.5 years, range 25±52) with nonbacterial prostatitis in whom clinical management was unsuccessful in relieving the symptoms or signs of prostatitis were treated using TUNA. All patients had a high leukocyte count (>15 per high-power ®eld) in expressed prostatic secretions (EPS) with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 19 publications
1
14
0
1
Order By: Relevance
“…An initial pilot study of 21 patients treated with TUNA demonstrated a significant improvement at 1-year follow-up [32]. Two further prospective studies demonstrated similar results over shorter follow-up periods of 3 months and 6 months, respectively [33,34]. Leskinen et al [35] performed a prospective, randomized, sham-controlled study of 33 patients that failed to show a significant difference between the TUNA group and sham group in pain score or quality of life at 12-month follow-up, raising doubts as to the effectiveness of this therapy.…”
Section: Transurethral Needle Ablationmentioning
confidence: 89%
“…An initial pilot study of 21 patients treated with TUNA demonstrated a significant improvement at 1-year follow-up [32]. Two further prospective studies demonstrated similar results over shorter follow-up periods of 3 months and 6 months, respectively [33,34]. Leskinen et al [35] performed a prospective, randomized, sham-controlled study of 33 patients that failed to show a significant difference between the TUNA group and sham group in pain score or quality of life at 12-month follow-up, raising doubts as to the effectiveness of this therapy.…”
Section: Transurethral Needle Ablationmentioning
confidence: 89%
“…Four patients showed complete resolution of symptoms and three reported partial improvement. A larger uncontrolled study was published by Lee et al [19]. Forty-two patients with CP who had failed standard treatments were included.…”
Section: Transurethral Needle Ablationmentioning
confidence: 99%
“…All of the patients had a decrease in the leukocyte count in EPS 1 month after treatment. More encouraging data came from an uncontrolled study of 42 patients with nonbacterial prostatitis (category IIIA) [44]. Seventy-eight percent of the patients had a satisfactory score using a nonvalidated symptom scale.…”
Section: Transurethral Needle Ablationmentioning
confidence: 99%